OP170 How Can Health Technology Assessment Participate In The Healthcare Quality Improvement?. (2019) - Allouche, Wafa; Gouddi, Sami El; Allouche, Emna; Mrabet, Ali
Abstract : Introduction: Providing high-quality and affordable care is a big challenge facing policy makers, especially in low and middle income countries (LMIC). The purpose of this presentation is to illustrate how health technology assessment (HTA) benefits the improvement of the healthcare quality, and to highlight the fact that HTA domains match to the dimensions of health quality: safety, effectiveness, efficiency and patient-centeredness. Methods: This presentation will be based on explaining the ability of HTA to improve the quality of healthcare. Some countries, mainly LMIC where resources are limited, do not have formal HTA whose goal is to inform the development of safe, effective and patient centered health policies. The theoretical concepts of HTA demonstrate a strong connection between HTA and healthcare quality improvement. By way of illustration an example of successful experiences will be given. Results: The presentation items are: - The definition of health technology - Introduction to health technology assessment as a multidisciplinary process that summarizes information about the medical, social, economic and ethical issues related to the use of a health technology. - Why is health technology assessment used, the identification of the HTA report domains including Safety, Clinical Effectiveness, Ethical analysis, Social aspects, Legal aspects and the importance of patient experience in HTA. - The identification of the six dimensions of healthcare quality and the determination of the connection between HTA and healthcare quality improvement. - A presentation of the international Decision Support Initiative (iDSI) experience in some LMIC. Conclusions: HTA has many meeting points with healthcare quality dimensions. HTA is likely to become an increasingly important influence in health decisions.